NELAYAN PENANGKAP HIU DI KECAMATAN KENDAHE KABUPATEN KEPULAUAN SANGIHE - Setiawan, Christian (HOLISTIK, Journal Of Social and Culture, 2013)
Fishermen who catch a shark can be categorized as a profession that requires special courage and skill. Because sharks are relatively harmless species of fish, sharks have a habit of attacking a fishermen. It's no exaggeration when among fellow fishermen, shark fishers not be underestimated. Both in terms of their courage to conquer the dangerous sharks as fish species, as well as in terms of economical, considering selling shark fin is quite high compared to other fish species. Distances that must be taken into Tahuna where the fish can be sold, make fisherman from Kawaluso village decide to selling fish at Matutuang island. But at the island of Matutuang, other types of fish less than Shark demand by buyers. Instead, shark have more value from the view of the buyer. Philippine ships almost every day at the island of Matutuang to bought sharks in large numbers. This is the main reason why the fishermen in the village of Kawaluso caught a shark. There are also other reasons why they choose shark as the principal source of their livelihood, have been described in this paper. Keywords: Fishing, Shark